Antibody-mediated rejection after liver transplantation-relevance of C1q and C3d-binding antibodies - Kovandova, Barbora; Slavcev, Antonij; Sekerkova, Zuzana; Honsova, Eva; Trunecka, Pavel (HLA, 2018)
The aim of our study was to evaluate the relevance of complement-binding donor-specific antibodies (DSA) for prediction of antibody-mediated rejection (AMR) after liver transplantation. Sera from 123 liver transplant recipients were retrospectively defined for HLA specificity and complement-fixing activity using the single antigen beads, C1q and C3d techniques. Liver-recipients' sera were tested before transplantation, 3, 6 months and 1 year after transplantation. Patients were followed up for graft survival and rejection incidence for 1 year after transplantation. All patients with pretransplant complement-binding DSA developed severe AMR after transplantation, while three recipients out of four, who produced de novo complement-fixing DSA, developed AMR. Definition of DSA with respect to complement-fixing activity may provide clinically relevant information about the risk of AMR after liver transplantation.
Keywords: crossmatch; Graft Rejection; Male; Complement C1q; Transplantation, Homologous; komplement C3d; dárci tkání; lidé středního věku; rejection; retrospektivní studie; homologní transplantace; Liver Transplantation; rejekce štěpu; transplantace jater; Graft Survival; Humans; Tissue Donors; Middle Aged; senioři; prognóza; mužské pohlaví; Complement C3d; Female; Prognosis; Isoantibodies; mladiství; následné studie; Histocompatibility Testing; liver transplantation; Aged; HLA; ženské pohlaví; Retrospective Studies; Follow-Up Studies; isoprotilátky; Adult; C4d; přežívání štěpu; Adolescent; dospělí; dítě; lidé; complement; komplement C1q; antibodies; testování histokompatibility; Child